Rowan Atkinson - Dessau, Bruce (London Orion Media, 1997)
This is a fully illustrated, affectionate celebration of Rowan Atkinson's career, published to coincide with the film "Mr Bean". Atkinson first came to prominence in "Not The Nine O'Clock News" and his natural acting ability set him up to achieve huge success as Blackadder.
Include Color Illustration
Keywords: Atkinson, Rowan -- Comedians -- Great Britain